KS18, a Mcl-1 inhibitor, improves the effectiveness of bortezomib and overcomes resistance in refractory multiple myeloma by triggering intrinsic apoptosis - Al-Odat, Omar S.; Elbezanti, Weam Othman; Gowda, Krishne; Srivastava, Sandeep K.; Amin, Shantu G.; Jonnalagadda, Subash C.; Budak-Alpdogan, Tulin; Pandey, Manoj K. (Frontiers in Pharmacology, 2024)
Despite a record number of clinical studies investigating various anti-myeloma treatments, the 5-year survival rate for multiple myeloma (MM) patients in the US is only 55%, and almost all patients relapse. Poor patient outcomes demonstrate that myeloma cells are "born to survive” which means they can adapt and evolve following treatment. Thus, new therapeutic approaches to combat survival mechanisms and target treatment resistance are required. Importantly, Mcl-1, anti-apoptotic protein, is required for the development of MM and treatment resistance. This study looks at the possibility of KS18, a selective Mcl-1 inhibitor, to treat MM and overcome resistance. Our investigation demonstrates that KS18 effectively induces cell death in MM by dual regulatory mechanisms targeting the Mcl-1 protein at both transcriptional and post-translational levels. Specifically, KS18 suppresses Mcl-1 activation via STAT-3 pathway and promotes Mcl-1 phosphorylation/ubiquitination/proteasome-dependent protein degradation (UPS). Significantly, KS18 triggered caspase-dependent apoptosis in MM patient samples and bortezomib-resistant cells, synergizing with venetoclax to boost apoptosis. KS18 promises to overcome bortezomib and venetoclax resistance and re-sensitize myeloma cells to chemotherapy. Furthermore, the study shows the tremendous impact of KS18 in inhibiting colony formation in bortezomib-resistant cells and demonstrates significant tumor shrinkage in KS18-treated NSG mice without notable toxicity signs after four weeks of therapy with a single acceptable dose each week, indicating its powerful anti-neoplastic and anti-resistance characteristics. This study strongly implies that KS18 may treat MM and provide new hope to patients who are experiencing recurrence or resistance.